TRADISI ANGONAN SAPEH PADA MASYARAKAT DESA LARANGAN LUAR PAMEKASAN DALAM PERSPEKTIF FIKIH - Moh Subhan; Fahmi Assulthoni (Ulumuna: Jurnal Studi Keilsman, 2021)
Thetradition of angonan sapeh cooperation is common among the people of the Larangan Luar Pamekasan Village. This traditionis still well maintained until now, because in it there are noble values, namely the attitude of helping and brotherhood. The purpose of this study is to find out the tradition of angonan sapeh cooperation carried out by the people of Larangan Luar Pamekasan Village in a fiqh perspective. This study uses a qualitative approach with the research subject being the people of Larangan Luar Village who collaborate with angonan sapeh. Data collection techniques using interviews and documentation. The data collected was then analyzed using a descriptive method. The results of the study show that the people of Larangan Luar Village not only view the angonan sapeh tradition as only business cooperation, but the reareal so values of mutual help and brotherhood. This tradition is in accordance with fiqh, withusing a contract.